(untitled) (Research, Society and Development, 2022)
This research aims to analyze the impacts of Social Isolation caused by the Covid-19 on the daily lives of families. The survey was conducted using 15 questions that were answered through the google forms application, the link was made available via WhatsApp in different groups of workers, to access the questionnaire it was necessary to authorize the survey in agreement with the Informed Consent Form. The questionnaire was available to be accessed for four days, the answers were compiled, analyzed and the results were evaluated with descriptive statistics. The majority of respondents are aged between 31 and 40 years old (45%), followed by people aged 41 to 50 years old (25%), the age group 51 to 60 (14%) and from 20 to 30 (11%). 66% of the people who participated in the survey were women and 34% men. The families were mostly made up of two working people, making up 45% of the total, it was observed that only 16% of families are supported exclusively by men while 20% of families are supported exclusively by women. Of the participants 84% stayed in home office more than 60 days during the pandemic. 80% agree with social isolation. 31% said they faced conflicts that already existed or that arose after the pandemic. Solidarity (50%) and fear (38%) were the most cited feelings. Regardless of the type of feelings, most participants express their feelings during the pandemic period and stated that they mostly agree with social isolation.